The Chemistry and Applications of Metal-Organic Frameworks - Furukawa, Hiroyasu; Cordova, Kyle E.; O'Keeffe, Michael; Yaghi, Omar M. (Science (American Association for the Advancement of Science), 2013)
Metal-organic frameworks are porous materials that can exhibit very high surface areas that have potential for applications such as gas storage and separation, as well as catalysis. Furukawa et al. ( 1230444 ) review the structures devised so far and discuss the design strategies that allow families of materials to be synthesized and modified with similar framework topology but vary in pore size and type of functional groups present on the linkers. Crystalline metal-organic frameworks (MOFs) are formed by reticular synthesis, which creates strong bonds between inorganic and organic units. Careful selection of MOF constituents can yield crystals of ultrahigh porosity and high thermal and chemical stability. These characteristics allow the interior of MOFs to be chemically altered for use in gas separation, gas storage, and catalysis, among other applications. The precision commonly exercised in their chemical modification and the ability to expand their metrics without changing the underlying topology have not been achieved with other solids. MOFs whose chemical composition and shape of building units can be multiply varied within a particular structure already exist and may lead to materials that offer a synergistic combination of properties.